Analisis Manajemen Pemeliharaan Gedung Kantor (Studi Kasus PT AST) - Khalilah, Haliza Putri; Christian Wiradendi Wolor; Marsofiyati (Aplikasi Administrasi: Media Analisa Masalah Administrasi, 2023)
Buildings that support office activity need to be well maintained. Without the maintenance, the building's structure function will suffer a decline over time. This study aims to identify the maintenance management activities of the building, the building maintenance schedule and the obstacles also the solutions in the maintenance of the office building at PT AST. It uses a qualitative descriptive approach by describe and analyze the problems found. Qualitative research is based on primary and secondary data. Primary data in the study are obtained by observation, interview, and documentation, while secondary data are obtained through books, previous studies, and research related articles. According to the study, PT AST has been regularly and frequently maintained the building, but the maintenance activities have not been optimal. This can be seen from the difficult access of office repository and some office machines scheduled for delay in maintenance. It would be better if PT AST was able to provide some items replacement to anticipate the damage and also work with third party procurement to perform repairs on a damaged items or chamber if needed.